Entrepreneurial Intention Ditinjau Dari Entrepreneurial Motivation Dan Education Mahasiswa Manajemen Universitas Ciputra - Feilany Tali; Liliana Dewi (BIP's JURNAL BISNIS PERSPEKTIF, 2016)
The purpose of this research is to know the influence of Entrepreneurial Motivation and Entrepreneurship Education toward Entrepreneurial Intention on Faculty of Business Management, Ciputra University. The sample were used 93 students. This research used a quantitative research, random sampling and data was collect by questionnaire. The analysis technique used correlation pearson, cronbach alpha, multiple linear regression, t test, F test, and classical assumptions test. The result of multiple linear regression analysis is Ŷ = 0,750 + 0,585X1 + 0,240 X2, that means entrepreneurial intention influenced by entrepreneurial motivation and entrepreneurship education. Based on the results of study, it was found: 1) entrepreneurial motivation have positive and significant impact on entrepreneurial intention; based on multiple linear regression analysis (t test), is known tcount> ttable (5.331> 1.818) and the significance value <0.05(0,000). 2) entrepreneurship education have positive and significant impact on entrepreneurial intention; based on multiple linear regression analysis (t test), is known tcount> ttable (3,077 > 1,818) and the significance value <0.05 (0,003). 3) entrepreneurial motivation and entrepreneurship education together have a strong influence and direction of entrepreneurial intention (44.6%), while 54.4% are influenced by other variables not examined by researcher.